A New Route for Direct Electroless Ni-P Plating on Magnesium Alloys - Xuân Vương, Bùi (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 2DO - 10.25073/2588-1140/vnunst.4507, 2017)
This report describes a new route for direct electroless Ni-P plating on magnesium alloys using nickel sulfate as the main salt component. The surface morphology, chemical composition and corrosion resistance of coatings were determined using SEM, EDX and electrochemical polarization techniques. Ni-P coatings with good corrosion resistance and high adhesion were obtained using this route and improved pretreatments. A mixture of H 3 PO 4 and HNO 3 was used as a pickling solution for Mg substrate pretreatment. A coarse surface was produced via the developed pickling procedure. A mechanical occlusive force is believed to exist between the coatings and the substrates. Twice activations, K 4 P 2 O 7 and NH 4 HF 2 as activation components, respectively, were applied for the pretreatment of magnesium alloy plating. An optimal F/O ratio on the Mg substrate surface was obtained by this pretreatment method. The activation film has insoluble partial fluorides which can depress the active points on substrate surface against the reaction of Mg with Ni 2+ and H + in the plating bath. A highly stable bath with pH 5 buffer was identified. The advantages of the developed process include chromium-free, low fluoride, and high bath stability. It is applicable for the production of motorcycle part plating.